P2X7 Receptor in Hematological Malignancies - De Marchi, Elena; Pegoraro, Anna; Adinolfi, Elena (Frontiers in Cell and Developmental Biology, 2021)
The P2X7 receptor is an ion channel gated by the nucleotide ATP, known for its role in immune responses and recently emerging as a critical onco-promoting factor. Lymphocytes, myeloid cells, and their precursors were among the first cells proved to express a functional P2X7 receptor; therefore, it is not surprising that lympho and myeloproliferative diseases, also known as hematological malignancies, were shown to be related in their insurgence and progression to P2X7 alterations. Here we overview established and recent literature relating P2X7 with the biological mechanisms underlying leukemias, lymphomas, and multiple myeloma development. Particular attention is paid to studies published in the very recent past correlating P2X7 with ATP concentration in the leukemic microenvironment and P2X7 overexpression to acute myeloid leukemia aggressiveness and response to chemotherapy. The described literature strongly suggests that P2X7 and its genetic variants could be regarded as potential new biomarkers in hematological malignancies and that both P2X7 antagonists and agonists could emerge as new therapeutic tools alone or in combination with traditional chemotherapy.